Analisis Pengelolaan Persediaan Bahan Baku Kedelai (Glycine Max L.) Pada Industri Tahu Pak Teguh Di Desa Harapan Bengkulu Tengah - Riani Sarpeka; Evi Andriani; Rika Dwi Yulihartika (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Pak Teguh Tofu Factory is an agro-industry located in Harapan Village, Pulau Beringin village, Pondok Kelapa Sub-District, Central Bengkulu Regency, which utilizes soybeana (Glycine max L) as the mairaw material in the tofu production process. The availability and management of soybean raw material inventory are important factors in ensuring the smooth production process and cost efficiency The purpose of this research was to determine the condition of soybean raw material inventory and analyze the inventory management applied at Pak Teguh Tofu Factory. The method used is descriptive analysis (exploratory) and quantitative analysis with the Economic Order Quantity (EOQ), Safety Stock Reorder Point (ROP), and Total Inventory Cost (TIC) methods. The results of the research indicate that the inventory system implemented is still conventional, with an average usage of 100 kg per day or 3,000 kg per month, an ordering frequency of 6 times per month, and an ordering cost of Rp900,000 per month. Based on the EOQ method, the optimal order quantity is 3,128 kg per order, with a frequency of approximately once every 30 days of production. The safety stock value is 120 kg and the reorder point is 420 kg. The total inventory cost using the EOQ method is Rp287,700 per 30-day period, lower than the actual system, thus reducing Inventory costs by Rp612,300 per month. The application of the EOQ, safery stock and reorder point methods has proven to be more efficient in managing soybean raw material inventory and supporting the smooth and sustainable tofu production process.